PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA DENGAN MEDIASI KOMPETENSI PADA GURU TAMAN KANAKâKANAK (TK) DI KABUPATEN REMBANG - Qurotul Ã¢Â€Â˜Aini, 1352020087; Tjahjaningsih, Endang (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research was conducted with the aim to test the influence of the leadership of the principal against the competency of teachers, influence the work environment against the competency of teachers, and the influence of the teachers Performance against the Leadership, the influence of the environment on performance of teachers, and pengarug on performance Competence of teachers. Later expected to increase quality of work for kindergarten teachers in the Regency of Rembang. The population in this research is a kindergarten teacher in Rembang amounted to 114 people. Researchers use the data in this study by using primary data.Â that is the data that researchers obtain directly from the source through the questionnaire. While secondary data is data which support or supplement the primary data. As for the method of data collection used in this study with a questionnaire that is the collection of data by means of the grant of the questions. There are two types of questionnaires, namely the open and the closed questionnaire questionnaire. Open questionnaire is a questionnaire that is presented in a simple to charge appropriate circumstances include: (1) gender, (2) educational level, (3) age, (4) the working period, (5) Position. The closed questionnaire is a questionnaire that is used to obtain data research variables. Data collection of Principal Leadership variable (X 1) work environment (X 2), competence of teachers (Y1) and (x 2) Teacher Performance using primary data. Results of the study prove that hypothesis to the leadership of the principal does not affect the competence, working environment and significant negative effect against the Leadership competence, positive and significant effect on performance, the working environment has no effect on performance, positive and influential teacher Competence significantly to performance. Keywords: Leadership, Work Environment, Competence And Performance